RELATIONSHIP BETWEEN SPIRITUAL INTELLIGENCE AND SUBJECTIVE WELL-BEING IN CIVIL SERVANT GROUP II DIPONEGORO UNIVERSITY - Brian Shendy Haryanto; Sri Hartati (Jurnal EMPATI, 2013)
Related to the ability to produce creative work of God in the lives of so-called spiritual intelligence, which has an important role to humans. Spiritual intelligence of the individual to create a close relationship with God and build relationships with fellow human beings and nature preserve. Spiritual intelligence will affect the way of thinking and how to solve problems that affect the emotional state of class II civil servants who then have an impact on subjective well-being. This study aims to determine the ties between spiritual intelligence with subjective well-being in the state of class II civil servants at the University of Diponegoro.The population in this study is the state of class II civil servants at the University of Diponegoro total of 157 people from a total of 327 civil servants number of class II. This study using proportional random sampling technique. Methods of data collection using psychological scales, the scale of subjective well-being and spiritual intelligence scale. Subjective well-being scale consists of 20 items valid (α = 0.798) and Spiritual Intelligence Scale with 27 aitem (α = 0.875). Data analysis was conducted using correlation analysis SpearmanThe results showed a correlation coefficient r xy = -0.327 with p = 0.079 (p <0.005) which means that there is no relationship between spiritual intelligence with subjective well-being.